Medication Profile and Side Effect - Severity of Anti-Tuberculosis Drugs in Pulmonary Tuberculosis Patient at Bhina Bhakti Husada Rembang Hospital - Nike Sri Wulandari; Endang Setyowati; Intan Adevia Rosnarita (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to identify the treatment profile and the type and severity of anti-tuberculosis drug (OAT) side effects in pulmonary tuberculosis patients at Bhina Bhakti Husada Rembang Hospital. It was hypothesized that most patients would receive first-line OAT regimens and experience side effects predominantly of moderate severity. Research Method: This study used a descriptive observational method with a cross-sectional design. Data were obtained retrospectively from the medical records of 106 patients with pulmonary tuberculosis receiving first-line OAT therapy at Bhina Bhakti Husada Rembang Hospital. The variables included patient characteristics, treatment patterns, types of OAT side effects, and severity of adverse drug reactions. Data were analyzed using univariate descriptive analysis. Results and Discussion: Most patients were aged 41-60 years (43.4%), male (64.2%), had a body weight of 30-49 kg (61.3%), and underwent treatment for 1-3 months (42.5%). The most common regimen was category 1 RHZE 2 FDC (39.6%). The most frequent side effects were reddish urine (100.0%), nausea and vomiting (83.0%), and flu syndrome (70.8%). Most side effects were categorized as moderate (56.6%). Implications: The findings emphasize the importance of routine monitoring and early management of OAT side effects, particularly during the early treatment phase. Further studies are needed to examine risk factors associated with severe adverse reactions and their impact on treatment adherence.